2019
DOI: 10.1038/s41467-019-10354-2
|View full text |Cite
|
Sign up to set email alerts
|

A toll-like receptor agonist mimicking microbial signal to generate tumor-suppressive macrophages

Abstract: Switching macrophages from a pro-tumor type to an anti-tumor state is a promising strategy for cancer immunotherapy. Existing agents, many derived from bacterial components, have safety or specificity concerns. Here, we postulate that the structures of the bacterial signals can be mimicked by using non-toxic biomolecules of simple design. Based on bioactivity screening, we devise a glucomannan polysaccharide with acetyl modification at a degree of 1.8 (acGM-1.8), which specifically activates toll-like receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(114 citation statements)
references
References 45 publications
4
104
0
1
Order By: Relevance
“…Toll-like receptors (TLRs) are normally activated by microbial moieties (including nucleic acids) allowing macrophages to acquire a M1 phenotype. Using a TLR agonist to reprogram macrophages was thus of interest in cancer treatment (Feng et al, 2019). Numerous TLR7 ligands, TLR9 ligands, and one TLR8 ligand have been tested for their antitumoral properties in clinical trials ( Table 2).…”
Section: Tlr Agonistmentioning
confidence: 99%
“…Toll-like receptors (TLRs) are normally activated by microbial moieties (including nucleic acids) allowing macrophages to acquire a M1 phenotype. Using a TLR agonist to reprogram macrophages was thus of interest in cancer treatment (Feng et al, 2019). Numerous TLR7 ligands, TLR9 ligands, and one TLR8 ligand have been tested for their antitumoral properties in clinical trials ( Table 2).…”
Section: Tlr Agonistmentioning
confidence: 99%
“…Among TLR family members, TLR2 activation of peripheral monocytes triggers differentiation into DC-SIGN+ macrophages, with robust M1 anti-tumoral phenotype 24 . Along the same line, recent work reports that acGM-1.8, a specific TLR-2 agonist, generates macrophages with strong anti-tumor potential in mice 8 . For TLR7, a recent report shows that R848, an agonist of TLR7 and TLR8, is a potent driver of the M1 phenotype in vitro and that R848-loaded nanoparticles target TAMs in vivo to impede colon tumor and melanoma growth in mice 25 .…”
Section: Discussionmentioning
confidence: 77%
“…On one hand, we found that CL347 treatment significantly decreases the number of lymphocytes infiltrating R211 tumors ( Fig. 5A and 5B); on the other hand, CL347 massively increases 8 the number of F4/80 positive cells in tumors ( Fig. 5A and 5C).…”
Section: Considering the Well-described Effect Of Tlr7 On Immune Cellmentioning
confidence: 82%
See 1 more Smart Citation
“…Then, stimulated adherence by E. coli LPS, lipid A and OK-432 may be explained by the increased expression of CD11b/CD18 through TLR4 and the increased adherence by N-CWS and lipoteicoic acid may be mediated by TLR-2 expressed in neutrophils in addition to macrophages. As activation of TLR4 and TLR2 are reported to be tumoricidal (11,39), antitumor mechanism of bacterial BRMs may depend on the activation of TLR4 and/or TLR2 expressed in neutrophil in addition to macrophage. So far, the mechanism of antitumor effect of BRM was explained mainly through the activation of macrophage (40).…”
Section: Discussionmentioning
confidence: 99%